Microbiota of the vagina and myoma nodes in uterine myoma - E. S. Nikitina; A. N. Rymashevsky; Y. L. Naboka; M. A. Rymashevsky; I. A. Gudima; E. G. Svirava (Медицинский вестник Юга России, 2022)
Objective: to study the microbiota of the vagina, myomatous nodes, their bed in patients with fibroids. Materials and methods: a comprehensive examination of 83 patients aged 26 to 50 years with diagnosed interstitial, interstitial-subserous uterine myoma was carried out. By age, all women are divided into 3 groups. Standard clinical and clinical laboratory studies, colposcopy, microbiological examination of the detachable posterior vaginal fornix, biopsy specimens of myomatous nodes and their bed, as well as morphological examination of biopsy specimens of myomatous nodes and their bed were performed.Results: in the structure of clinical manifestations of uterine fibroids, pain syndrome was the leading one (p<0.05). The number of myoma nodes in patients varied from 1 to 22. The duration of the operation and the amount of blood loss did not differ significantly (p>0.05). According to the results of a bacteriological study of the detachable posterior vaginal fornix in patients in the 2nd group, a decrease in the frequency of detection and the number of lactobacilli was revealed compared to the 1st group, and in women in the 3rd group, these microorganisms were absent. Among the anaerobic microorganisms in the 1st and 2nd groups, Eubacterium spp. dominated, in the 3rd — Peptostreptococcus spp. In patients of group 3, the frequency of detection of Bacteroides spp. was significantly increased (p<0.05). Among the aerobic spectrum of microorganisms in all groups, coagulasenegative staphylococci predominated. In a bacteriological study of biopsy specimens, the absence of growth of microorganisms in myomatous nodes was observed in 7.2% of cases, in the tissue of the bed of myomatous nodes in 17.7%. The microbiota of myomatous nodes and their bed in most cases was represented by anaerobic taxa. According to the results of a morphological study of biopsy specimens, no inflammatory reaction of tissues was detected. Conclusions: In women with uterine myoma of different age groups, multidirectional changes in the vaginal microbiota were revealed. In most cases, the myomatous node (92.8%) and its bed (82.3%) are not sterile with the dominance of anaerobic microbiota taxa. Identified significant correlations in the loci «vagina – myomatous node – myomatous node bed» indicate their relationship. The detection of various taxa of microorganisms in the myomatous node and its bed, according to morphological studies, is not associated with the presence of infectious and inflammatory processes in the tissues.